Efesiensi Penerapan Kurikulum pada Pendidikan Islam di Era Globalisasi dalam Perspektif Ahmad Rusydi Thu’aimah - Sukron; Muhlis, Achmad; Jasuli; Iklilullah (STIT Fatahillah, 2025)
This study aims to analyze the efficiency of curriculum implementation in Islamic education in the era of globalization, using Ahmad Rusydi Thu’aimah's perspective as the theoretical basis. The research method used is a literature review enriched with a comparative analysis of various previous studies from the reputable journal SINTA. The results indicate that Thu’aimah's curriculum principles, including material relevance, functional content selection, a communicative learning approach, and competency orientation, are highly relevant in improving the efficiency of the Islamic education curriculum. The integration of Islamic values with 21st-century competencies has proven to produce a curriculum that is adaptive, effective, and maintains Islamic identity. However, the implementation of an efficient curriculum faces several obstacles, such as low teacher digital literacy, resistance to innovation, and limited technological resources in some Islamic educational institutions. This study confirms that implementing Ahmad Rusydi Thu’aimah's curriculum principles can be a strategic solution to strengthen the quality and competitiveness of Islamic education amidst global challenges